The Impact of a Structured Virtual Reality Simulation Training Curriculum for Novice Endoscopists - Mendes,Sofia Silva (2022)
Abstract Background: Current evidence supports the use of virtual reality (VR) simulation-based training for novice endoscopists. However, there is still a need for a standardized induction programme which ensures sufficient preparation, with knowledge and basic skills, before their approach to patient-based training. We designed a structured progressive programme in upper endoscopy and colonoscopy and aimed to determine its impact on cognitive and technical performance. Methods: Prospective, multicentre study, focused on “Endoscopy I, 2018,” a course with a theoretical and a hands-on module (20 h) in the GI Mentor II®. Gastroenterology residents of the 1st year were enrolled. A pre-test and test were applied to evaluate the cognitive component, and a pre-training and post-training esophagogastroduodenoscopy (EGD) and colonoscopy VR cases were used to evaluate the technical component. The hands-on training included psychomotor exercises (Navigation I, Endobubble I), 4 EGD, and 4 colonoscopy VR cases. The metrics applied for technical skills evaluation were time to reach the second portion of duodenum (D2)/cecum (seconds), efficiency of screening (%), and time the patient was in pain (%). Results: Twenty-three participants were included, majority female (67%), 26 ± 0.7 years old. Comparing the pre-test versus test, the cognitive score significantly improved (11/15 vs. 14/15; p < 0.001). Considering the technical assessment after training: in EGD, the time to D2 was significantly lower (193 vs. 63 s; p < 0.001), and the efficiency of screening significantly better (64 vs. 91%; p < 0.001); in colonoscopy, the time to reach the cecum was significantly lower (599 vs. 294 s; p = 0.001), the time the patient was in pain was significantly lower (27 vs. 10%; p = 0.005), and the efficiency of screening had a tendency towards improvement (50 vs. 68%; p = 0.062). Conclusion: The proposed training curriculum in basic endoscopy for novices is aligned with international recommendations and demonstrated a significant impact on cognitive and technical skills learning achievements.